HUBUNGAN SUPERVISI PENGAWAS TERHADAP KINERJA DAN PROFESIONALISME GURU BIDANG STUDI FISIKA PADA SMA TELADAN WAY JEPARA - sugiono sugiono (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2016)
The supervision of the development activities planned to help teachers and school employees to do the job effectively. And the performance of teachers in the learning process are: Perform or teachers' skills in creating an atmosphere of educational communication between teachers and learners that includes the atmosphere of cognitive, affective and psychomotor as an attempt to learn planning by something to the stage of evaluation and follow-up to achieve the goal of teaching , Teacher professionalism is the commitment, where teachers are really committed to the teaching profession. Based on the concept above means regulatory oversight, dealing with the performance, supervision related to teacher professionalism ".This research problems" Is there a relationship between regulatorysupervision and professional performance of teachers? ". The aim is to" analyze the relationship between supervisor supervision's Performance and professionalism of teachers ". Hypotheses Research" There is a significant relationship between supervision with the performance and professionalism of teachers ", the study population is" All teachers Subjects physics in high school Exemplary Way Jepara, using product moment correlation analysis: concluded that "There is a significant relationship between supervision with the performance and professionalism of teachers". Keyword: Supervision, Performance and Professionalism